A Comparative Analysis of Perceptions held towards African Female Leaders, Successful Middle Managers, Females, and Males in the Financial Services Industry - Sanelisiwe Moleko, Zandile; I. Ukpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2020)
The representation of African females in leadership positions is limited in the South African context. Leadership research indicates several barriers encountered by females in advancing into leadership roles due to pervasive negative perceptions of African females as leaders. The stereotypes held of females’ impact on their ability to be represented in leadership roles. The phenomenon of ‘think manager, think male,’ identified by Schein, reinforces the conviction that female leadership is less likely to be effective, thus drawing a correlation between characteristics attributed to managers and those attributed to males being considered superior to those of female managers. This paper provides a comparison of the perceptions held towards African female leaders, successful middle managers, females, and males within the financial services industry. A mixed-methods approach was employed, with the first phase being composed of the distribution of Schein’s Descriptive Index (SDI) and the second phase composed of interviews with African female leaders, their subordinates, peers, and managers. The results indicate that there is a significant difference in respondents’ perceptions of African female leaders, females, successful middle managers, and males in the financial services industry.